Design and build motion graphics video about Information Security ISMS (Information Security Management System) of Cloud Technology Co., Ltd - Nguyen, Thi Trang (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Multimedia Communication; 2020 - 2025